A polymer thickener and its preparation method and application

By using quaternary polymer thickening agent, the problem of unstable viscosity of existing thickening agents under high temperature and high salt conditions is solved, and a polymer thickening agent with high viscosity and shear resistance is achieved. It is suitable for Ultra-deep wells and seawater fracturing reduce dissolution time and energy consumption.

CN119161533BActive Publication Date: 2025-02-11DONGYING ZHONGYUE PETROLEUM TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411657841.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-11
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The existing fracturing liquid thickening agent has unstable viscosity under high temperature and high salt conditions and is used in large quantities, which affects the fracturing effect and economicality.

Method used

Using a quaternary polymer thickening agent, synthesized by a one-pot method, including N-acryloyl (trihydroxymethyl)aminomethane, perfluorooctylethylacrylate, 1-vinyl-2-pyrrolidone and monomers such as N,N'-diallyl-L-tartrate diamine, have high apparent viscosity and shear resistance.

Benefits of technology

It achieves high viscosity stability under high temperature and high salt conditions, reduces dissolution time and energy consumption, is suitable for ultra-deep well fracturing and seawater fracturing, and is used in small amounts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention belongs to the field of oil production technology, and specifically relates to a polymer thickener and its preparation method and application. The preparation method is as follows: N-acryloyl (trimethylol) aminomethane, deionized water, hydroxyethyl cellulose, dodecylphenol polyoxyethylene ether, and buffer salt are sequentially added in a reactor, stirred evenly, perfluorooctyl ethyl acrylate, 1-vinyl-2-pyrrolidone, N, N'-diallyl-L-tartaric acid diamine are sequentially added, stirred evenly, and pH is adjusted to 7-8; an initiator is added to a high-position drop-adding tank, and after the drop-adding is completed, the reaction is kept warm to obtain a viscous liquid; the above-mentioned viscous liquid is dried and granulated to obtain a product thickener. The present invention has the advantages of simple synthesis, high apparent viscosity, strong shear resistance, and good drag reduction effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petroleum extraction, and in particular relates to a polymer thickener and a preparation method and application thereof. Background Art

[0002] As one of the important technologies for increasing oil and gas production, hydraulic fracturing technology has received widespread attention. At the same time, fracturing is increasingly used in major oil fields as a measure to improve the production of low-permeability reservoirs, and the development of fracturing fluid is also getting faster and faster. Fracturing fluid is the core of fracturing transformation. In the fracturing process, it plays a role in transmitting pressure, carrying proppant, and enhancing fracture-making ability, which can improve the conductivity of oil and gas.

[0003] The fracturing fluid used in fracturing must have high viscosity, high shear resistance, high sand carrying capacity, etc. Thickener is the main agent of water-based fracturing fluid, which is used to increase the viscosity of fracturing fluid, reduce fracturing fluid loss, suspend and carry proppant.

[0004] There are many types of thickeners, mainly guar gum, viscoelastic surfactants and synthetic polymers. Guar gum and its derivatives are widely used, but they are expensive and have a high insoluble content, which causes great damage to the surface. Synthetic polymer thickeners are widely available and have the advantages of high thickening ability, good temperature resistance, low residue rate, and good sand carrying capacity, becoming a hot spot in fracturing fluid research.

[0005] CN1073194A discloses a fracturing fluid thickener, which is suitable for fracturing and transformation of low permeability oil and gas layers. It is made by chemically modifying the herbaceous plant Tendril powder with ethanol, caustic soda, propylene oxide and water. However, the fracturing fluid thickener contains a high amount of residue and has poor temperature resistance.

[0006] CN113372516A provides a thickener superfine powder, a giant arm type thickener and its preparation method and application. The giant arm type thickener provided by the present invention comprises the following components by weight: 500-650 parts of thickener superfine powder, 5-10 parts of suspending agent, 2-5 parts of activator, 5-10 parts of shearing agent, 5-10 parts of emulsifying dispersant, and 325-480 parts of white oil; the giant arm type thickener provided by the invention forms a molecular chain structure with a shorter main molecular chain but a thick and long side chain structure, changes the viscoelasticity of the polymer, and under high temperature and high salt conditions, the polymer has extremely high viscosity, and its thermal stability is excellent, which can be adapted to ultra-deep well fracturing construction operations with a temperature of 220°C, and the dissolution speed is extremely fast, and it can be completely dissolved in 3 minutes, which significantly shortens the dissolution time and reduces the energy consumption caused by the dissolved product, and is adapted to seawater and produced water online fracturing construction operations. However, the stability of the suspension system is slightly poor, and the amount of the thickener used is relatively large. Summary of the invention

[0007] The present invention aims at the above-mentioned deficiencies of the prior art and provides a polymer thickener and a preparation method and application thereof. The present invention has the advantages of simple synthesis, high apparent viscosity, strong shear resistance and good drag reduction effect.

[0008] One of the purposes of the present invention is to disclose a method for preparing a polymer thickener, the specific steps of which are as follows:

[0009] (1) Add N-acryloyl (trihydroxymethyl) aminomethane, deionized water, hydroxyethyl cellulose, dodecylphenol polyoxyethylene ether, and buffer salt to the reactor in sequence, stir evenly, purge the reactor and pipeline with nitrogen to replace the air in the reactor, then add perfluorooctyl ethyl acrylate, 1-vinyl-2-pyrrolidone, and N,N′-diallyl-L-tartaric acid diamine in sequence, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;

[0010] (2) Add the initiator to the high-position drop tank. After the addition is completed, continue stirring until the viscosity begins to rise. Continue stirring for 30-60 minutes, continue to heat to 60-65°C, and keep the temperature for 30-60 minutes to obtain a viscous liquid.

[0011] (3) Drying and granulating the viscous liquid to obtain a polymer thickener.

[0012] In the present invention, preferably, the molar ratio of perfluorooctyl ethyl acrylate, 1-vinyl-2-pyrrolidone, N,N′-diallyl-L-tartaric acid diamine and N-acryloyl (trihydroxymethyl) aminomethane is 0.2-0.4:0.1-0.2:0.05-0.1:1.

[0013] In the present invention, preferably, in step (1), the weight ratio of deionized water, hydroxyethyl cellulose, dodecylphenol polyoxyethylene ether, and N-acryloyl (trihydroxymethyl) aminomethane is 8-10: 0.05-0.1: 0.05-0.1: 1.

[0014] In the present invention, preferably, in step (1), the buffer salt is one of potassium dihydrogen phosphate, sodium dihydrogen phosphate, and ammonium dihydrogen phosphate, and the weight ratio of the buffer salt to N-acryloyl(trihydroxymethyl)aminomethane is 0.02-0.04:1.

[0015] In the present invention, preferably, in step (2), the initiator is a mixed solution of persulfate and sodium bisulfite, wherein the concentration of persulfate is 10-12wt%, the concentration of sodium bisulfite is 4-6wt%, and the weight ratio of initiator to acrylamide is 0.2-0.4:1.

[0016] Preferably, the persulfate is one of potassium persulfate, ammonium persulfate and sodium persulfate.

[0017] The polymer thickener synthesis reaction equation of the present invention is as follows:

[0018]

[0019]

[0020] Another object of the present invention is to disclose a polymer thickener, the structural formula of the polymer thickener is as follows:

[0021]

[0022] in:

[0023] m=10000-100000;

[0024] n = 2000-40000;

[0025] p = 1000-20000;

[0026] o=500-10000.

[0027] In the present invention, preferably, the viscosity average molecular weight of the polymer thickener is 15,000,000-20,000,000.

[0028] The third object of the present invention is to disclose the application of the above polymer thickener in low permeability reservoir fracturing.

[0029] The polymer thickener of the present invention is a quaternary high molecular polymer. The main monomer of the polymerization is N-acryloyl (trimethylol) aminomethane, which contains amino groups and a large number of hydroxyl groups, and can be cross-linked with various cross-linking agents; perfluorooctyl ethyl acrylate can reduce surface interfacial tension, can reduce friction resistance, and play a role similar to slippery water; the molecule contains 1-vinyl-2-pyrrolidone, which can increase shear resistance; N, N'-diallyl-L-tartaric acid diamine, which makes the polymer present a two-dimensional or three-dimensional structure, which can greatly increase the viscosity of the molecule, and contains amino groups and hydroxyl groups, which is easy to cross-link, thereby increasing the viscosity of the product and improving the fracturing effect. Hydroxyethyl cellulose plays the role of a dispersant in the polymerization process, improving the polymerization effect of the present invention, and also can enhance the cross-linking effect.

[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0031] (1) The polymer thickener of the present invention is synthesized by a one-pot method, the synthesis process is simple, and there are no by-products;

[0032] (2) The polymer thickener of the present invention has a relatively high apparent viscosity, with a viscosity of 115 mPa•s or above at a concentration of 2000 mg / L; it has good shear resistance, with a viscosity of 170 s or above. -1 Under the conditions of , after continuous shearing for 120 minutes, the viscosity retention rate reached more than 87%; the configured fracturing fluid had a good drag reduction rate, which reached more than 86%. DETAILED DESCRIPTION

[0033] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0034] Example 1

[0035] (1) Add 0.1 mol N-acryloyl (trihydroxymethyl) aminomethane, 140 g deionized water, 0.88 g hydroxyethyl cellulose, 0.88 g dodecylphenol polyoxyethylene ether, and 0.35 g sodium dihydrogen phosphate to the reactor in sequence, stir evenly, purge the reactor and pipeline with nitrogen to replace the air in the reactor, then add 0.02 mol perfluorooctyl ethyl acrylate, 0.02 mol 1-vinyl-2-pyrrolidone, and 0.01 mol N,N′-diallyl-L-tartaric acid diamine in sequence, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;

[0036] (2) Add 3.5 g of initiator into the high-position dropping tank. The initiator is a mixture of 12 wt% sodium persulfate and 6 wt% sodium bisulfite. After the addition is completed, continue stirring until the viscosity begins to increase. Continue stirring for 30 minutes, continue to heat to 65°C, and keep the temperature for 30 minutes to obtain a viscous liquid.

[0037] (3) Drying and granulating the viscous liquid to obtain a polymer thickener.

[0038] Example 2

[0039] (1) Add 0.1 mol N-acryloyl (trihydroxymethyl) aminomethane, 155 g deionized water, 1.44 g hydroxyethyl cellulose, 1.22 g dodecylphenol polyoxyethylene ether, and 0.45 g sodium dihydrogen phosphate to the reactor in sequence, stir evenly, purge the reactor and pipeline with nitrogen to replace the air in the reactor, then add 0.025 mol perfluorooctyl ethyl acrylate, 0.018 mol 1-vinyl-2-pyrrolidone, and 0.009 mol N,N′-diallyl-L-tartaric acid diamine in sequence, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;

[0040] (2) Add 4.8 g of initiator into the high-position dropping tank. The initiator is a mixture of 11 wt% sodium persulfate and 5 wt% sodium bisulfite. After the addition is completed, continue stirring until the viscosity begins to increase. Continue stirring for 60 min, continue heating to 60 ° C, and keep the temperature for 60 min to obtain a viscous liquid.

[0041] (3) Drying and granulating the viscous liquid to obtain a polymer thickener.

[0042] Example 3

[0043] (1) Add 0.1 mol N-acryloyl (trihydroxymethyl) aminomethane, 166 g deionized water, 1.52 g hydroxyethyl cellulose, 1.75 g dodecylphenol polyoxyethylene ether, and 0.52 g diammonium phosphate to the reactor in sequence, stir evenly, purge the reactor and pipeline with nitrogen to replace the air in the reactor, then add 0.03 mol perfluorooctyl ethyl acrylate, 0.016 mol 1-vinyl-2-pyrrolidone, and 0.008 mol N,N′-diallyl-L-tartaric acid diamine in sequence, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;

[0044] (2) Add 7 g of initiator into the high-position dropping tank. The initiator is a mixture of 10 wt% potassium persulfate and 4 wt% sodium bisulfite. After the addition is completed, continue stirring until the viscosity begins to increase. Continue stirring for 50 min, continue heating to 62 ° C, and keep the temperature for 55 min to obtain a viscous liquid.

[0045] (3) Drying and granulating the viscous liquid to obtain a polymer thickener.

[0046] Example 4

[0047] (1) Add 0.1 mol N-acryloyl (trihydroxymethyl) aminomethane, 175 g deionized water, 1.75 g hydroxyethyl cellulose, 1.71 g dodecylphenol polyoxyethylene ether, and 0.47 g diammonium phosphate to the reactor in sequence, stir evenly, purge the reactor and pipeline with nitrogen to replace the air in the reactor, then add 0.033 mol perfluorooctyl ethyl acrylate, 0.014 mol 1-vinyl-2-pyrrolidone, and 0.007 mol N,N′-diallyl-L-tartaric acid diamine in sequence, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;

[0048] (2) Add 6.4 g of initiator into the high-position dropping tank. The initiator is a mixture of 10 wt% potassium persulfate and 4 wt% sodium bisulfite. After the addition is completed, continue stirring until the viscosity begins to increase. Continue stirring for 60 min, continue heating to 60 ° C, and keep the temperature for 40 min to obtain a viscous liquid.

[0049] (3) Drying and granulating the viscous liquid to obtain a product thickener.

[0050] Example 5

[0051] (1) Add 0.1 mol N-acryloyl (trihydroxymethyl) aminomethane, 168 g deionized water, 1.17 g hydroxyethyl cellulose, 1.25 g dodecylphenol polyoxyethylene ether, and 0.61 g potassium dihydrogen phosphate to the reactor in sequence, stir evenly, purge the reactor and pipeline with nitrogen to replace the air in the reactor, then add 0.036 mol perfluorooctyl ethyl acrylate, 0.012 mol 1-vinyl-2-pyrrolidone, and 0.006 mol N,N′-diallyl-L-tartaric acid diamine in sequence, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;

[0052] (2) Add 5.2 g of initiator into the high-position dropping tank. The initiator is a mixture of 11 wt% ammonium persulfate and 5 wt% sodium bisulfite. After the addition is completed, continue stirring until the viscosity begins to increase. Continue stirring for 60 min, continue heating to 60 ° C, and keep the temperature for 60 min to obtain a viscous liquid.

[0053] (3) Drying and granulating the viscous liquid to obtain a polymer thickener.

[0054] Example 6

[0055] (1) Add 0.1 mol N-acryloyl (trihydroxymethyl) aminomethane, 155 g deionized water, 1.58 g hydroxyethyl cellulose, 1.33 g dodecylphenol polyoxyethylene ether, and 0.7 g potassium dihydrogen phosphate to the reactor in sequence, stir evenly, purge the reactor and pipeline with nitrogen to replace the air in the reactor, then add 0.04 mol perfluorooctyl ethyl acrylate, 0.01 mol 1-vinyl-2-pyrrolidone, and 0.005 mol N,N′-diallyl-L-tartaric acid diamine in sequence, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution;

[0056] (2) Add 5.5 g of initiator into the high-position dropping tank. The initiator is a mixture of 11 wt% ammonium persulfate and 5 wt% sodium bisulfite. After the addition is completed, continue stirring until the viscosity begins to increase. Continue stirring for 45 minutes, continue to heat to 62°C, and keep the temperature for 40 minutes to obtain a viscous liquid.

[0057] (3) Drying and granulating the viscous liquid to obtain a polymer thickener.

[0058] Example 7 Test of apparent viscosity

[0059] The present invention uses 2 wt% sodium chloride solution to prepare a solution with a concentration of 2000 mg / L, and heats for 170 s at 60 °C. -1 Under the conditions of , the apparent viscosity μ0 is tested using DV-III Brookfield viscosity test.

[0060] The thickener produced by Shandong Maofa Chemical Co., Ltd. was used as a comparative sample. The test results are shown in Table 1.

[0061] It can be seen from Table 1 that the polymer thickener of the present invention (Examples 1-6) has a relatively high apparent viscosity, with the viscosity at a concentration of 2000 mg / L reaching 115 mPa•s and above, and a maximum of 120 mPa•s (Example 2); while the apparent viscosity of the comparative thickener is 45 mPa•s, which is significantly lower than that of the present invention.

[0062] Example 8 Shear resistance test

[0063] The solution of Example 7 was heated at 60°C for 170 seconds. -1 Under the conditions of continuous shearing for 120 minutes, the apparent viscosity μ1 was tested.

[0064] The shear resistance is denoted as η1,

[0065] η1=μ1 / μ0× 100%

[0066] The thickener produced by Shandong Maofa Chemical Co., Ltd. was used as a comparative sample. The test results are shown in Table 1.

[0067] It can be seen from Table 1 that the polymer thickener of the present invention (Examples 1-6) has good shear resistance. -1 Under the conditions of , after continuous shearing for 120 minutes, the viscosity retention rate reaches more than 87%, and the highest reaches 90% (Example 1); while the viscosity retention rate of the comparative thickener is 56%, which is significantly lower than that of the present invention.

[0068] Example 9 Drag reduction test

[0069] The present invention uses 2wt% sodium chloride solution to prepare a solution with a concentration of 2000mg / L, and adds borax solution (equivalent to a borax concentration of 0.05%), and the drag reduction rate η2 is tested with reference to the method in SY / T 6376-2008 "General Technical Conditions for Fracturing Fluids".

[0070] The thickener produced by Shandong Maofa Chemical Co., Ltd. was used as a comparative sample. The test results are shown in Table 1.

[0071] Table 1 Test results of apparent viscosity, shear resistance and drag reduction rate

[0072]

[0073] It can be seen from Table 1 that the fracturing fluid prepared with the polymer thickener of the present invention (Examples 1-6) has a good drag reduction rate, which is over 86%, and the highest is 89.3% (Example 6); while the drag reduction rate of the comparative thickener is 75.9%, which is significantly lower than that of the present invention.

[0074] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0075] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0076] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a polymer thickener, characterized in that: The specific steps of the preparation method are as follows: (1) Add N-acryloyl (trihydroxymethyl) aminomethane, deionized water, hydroxyethyl cellulose, dodecylphenol polyoxyethylene ether, and buffer salt to the reactor in sequence, stir evenly, purge the reactor and pipeline with nitrogen to replace the air in the reactor, then add perfluorooctyl ethyl acrylate, 1-vinyl-2-pyrrolidone, and N,N′-diallyl-L-tartaric acid diamine in sequence, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution; (2) Add the initiator to the high-position drop tank. After the addition is completed, continue stirring until the viscosity begins to rise. Continue stirring for 30-60 minutes, continue to heat to 60-65°C, and keep the temperature for 30-60 minutes to obtain a viscous liquid. (3) drying and granulating the viscous liquid to obtain a polymer thickener; The molar ratio of perfluorooctyl ethyl acrylate, 1-vinyl-2-pyrrolidone, N,N′-diallyl-L-tartaric acid diamine and N-acryloyl (trimethylol) aminomethane is 0.2-0.4: 0.1-0.2: 0.05-0.1: 1; The structural formula of the polymer thickener is as follows: , in: m=10000-100000; n=2000-40000; p=1000-20000; o=500-10000。 2. The preparation method according to claim 1, characterized in that: In step (1), the weight ratio of deionized water, hydroxyethyl cellulose, dodecylphenol polyoxyethylene ether and N-acryloyl (trihydroxymethyl) aminomethane is 8-10: 0.05-0.1:0.05-0.1:1。 3. The preparation method according to claim 1, characterized in that: In step (1), the buffer salt is one of potassium dihydrogen phosphate, sodium dihydrogen phosphate, and ammonium dihydrogen phosphate, and the weight ratio of the buffer salt to N-acryloyl (trihydroxymethyl) aminomethane is 0.02-0.04:

1.

4. The preparation method according to claim 1, characterized in that: In step (2), the initiator is a mixed solution of persulfate and sodium bisulfite, wherein the concentration of persulfate is 10-12wt% and the concentration of sodium bisulfite is 4-6wt%.

5. The preparation method according to claim 4, characterized in that: The persulfate is one of potassium persulfate, ammonium persulfate and sodium persulfate.

6. The polymer thickener prepared by the preparation method according to any one of claims 1 to 5, wherein the structural formula of the polymer thickener is as follows: , in: m=10000-100000; n=2000-40000; p=1000-20000; o=500-10000。 7. The polymer thickener according to claim 6, characterized in that: The viscosity average molecular weight of the polymer thickener is 15,000,000-20,000,000.

8. Use of the polymer thickener according to claim 6 or 7 in low permeability reservoir fracturing.

Citation Information

Patent Citations

  • Fracturing fluid thickening agent

    CN1073194A

  • Thickening agent ultrafine powder, giant-arm type thickening agent and preparation method and application of giant-arm type thickening agent

    CN113372516A

  • Polymer thickening agent for salt-resistant fracturing and synthesis method thereof

    CN117069888A

  • Polymer type acid liquor thickening agent and preparation method thereof

    CN117487085A